Female Agency in The Novel Sold (2006) by Patricia MacCormick - Sherynn Delaneira Wongkaren; Delvi Wahyuni (English Language and Literature, 2021)
This is an analysis of the novel entitled Sold (2006) written by Patricia MacCormick. This analysis looks at the agency shown by female characters in the novel who suffered because of patriarchy in Nepal. This analysis uses the concept of agency seen from feminist perspective. The analysis focuses on the agency form shown by female characters. This analysis uses fictional devices such as setting, plot, character to discover the issue. The result of the study shows female character shown agency in the form of intrinsic agency, self-definition and self-direction.